Fiber type-specific expression of LACTB leverages a function in oxidative metabolism - Kirsi-Marja Alanen; Rabah Soliymani; Jaakko Sarparanta; Satu Kuure; Kirsi Sainio; Zydrune Polianskyte; Muhammad Yasir Asghar; Ehsan Zangene; Annunziata Cascone; Maciej Lalowski; Peter Hackman; Johan Lundin; et al. (Histochemistry and Cell Biology, 2026)
Skeletal muscle is composed of type I and type II fibers, each characterized by specific metabolic machinery. LACTB is a conserved mitochondrial protein implicated in lipid utilization and tumorigenesis, but its precise function in the cellular metabolism remains unclear. To gain novel insight into the functional role of LACTB, we investigated skeletal muscle to determine whether LACTB is segregated by fiber type. The expression of LACTB was determined by immunohistochemistry (IHC) and immunoblotting in skeletal muscle from healthy human subjects and the laboratory rat. The specificity of the antibody was assessed using recombinant human LACTB protein and endogenous LACTB in isolated mitochondria. IHC results were validated in a cellular model of myoblast differentiation using the C2C12 and L6 cell lines. The results demonstrated that LACTB is highly enriched in adult type I muscle fibers. During development, LACTB expression commences in type I primary myotubes at the time of their formation around week 20 of gestational age. LACTB expression in myoblasts is low but increases rapidly upon the induction of myotube differentiation. We conclude that LACTB plays a distinct role in mitochondria of type I fibers, most likely acting in oxidative metabolism related to energy use from lipids. This defines LACTB as a mitochondrial marker for type I fibers.

Optimizing 2D in vitro differentiation conditions for C2C12 murine myoblasts on gelatin hydrogel - Veronica Sian; Per Harald Jonson; Anna Vainio; Helena Luque; Swethaa Natraj Gayathri; Peter Hackman; Bjarne Udd; Marco Savarese; Jaakko Sarparanta (Journal of Muscle Research and Cell Motility, 2025)
Optimizing in vitro differentiation protocols for skeletal muscle cells is essential for producing mature, functional myotubes suitable for disease modeling and therapeutic screening. While C2C12 murine myoblasts are a widely used model, achieving consistent and advanced differentiation remains challenging. In this study, we systematically evaluated conditions that improve myotube formation and maturation in a 2D culture system using ultra-compliant gelatin hydrogels. We compared standard and commercial differentiation media and identified that supplementation of DMEM with 2% horse serum and 10% Opti-MEM (DMO) supported robust myotube formation, with thin and aligned fibers. Insulin supplementation significantly increased expression of myosin heavy chain (MyHC) and calsequestrin, while pyruvate provided additional benefit by further enhancing myotube maturation. Media change frequency was also critical: daily replacement was necessary to maintain optimal differentiation, although the addition of insulin and pyruvate partly mitigated the effects of less frequent changes. Application of electrical pulse stimulation (EPS) improved sarcomeric α-actinin organization without significantly altering MyHC isoform expression. RNA sequencing confirmed transcriptional reprogramming consistent with myogenic progression, including early upregulation of key muscle-specific genes. Our findings present a cost-effective, reproducible protocol that supports advanced C2C12 differentiation in a scalable 2D system, offering practical guidance for generating mature, functional myotubes in vitro for both basic and translational muscle research.

Targeted Next-Generation Sequencing Reveals Novel TTN Mutations Causing Recessive Distal Titinopathy - Anni Evilä; Johanna Palmio; Anna Vihola; Marco Savarese; Giorgio Tasca; Sini Penttilä; Sara Lehtinen; Per Harald Jonson; Jan De Bleecker; Peter Rainer; Michaela Auer-Grumbach; Jean Pouget; et al. (Molecular Neurobiology, 2017)